Transatlantic Telerobotic Coronary Angiography - Ryan D. Madder, MD; Stacie VanOosterhout, MEd; Jessica L. Parker, MS; Alessandro Candreva, MD (JACC: Advances)
Background: Patients in many underserved geographies lack access to invasive coronary angiography (ICA). Objectives: This preclinical study explored the feasibility of telerobotic ICA between separate continents. Methods: Using a novel robotic system, attempts were made to navigate a magnetic guidewire and diagnostic catheter from the aortic arch into a target coronary artery ostium in a fluid-filled cardiac model. The model and robotic system were located in Zürich, Switzerland. The operating physician was either “onsite” in the laboratory in Zürich or “transatlantic,” in which the physician remotely controlled the robot from Grand Rapids, Michigan, USA. An onsite control group of 40 manual catheterization cases was made for comparison. The primary endpoint was technical success (catheter engagement into target ostium without conversion to manual). A secondary endpoint was engagement time (time from initial robotic manipulation to engagement in target ostium). Results: In 260 consecutive attempts, of which 40 (15.4%) were “onsite” and 220 (84.6%) were “transatlantic,” technical success was 97.5% onsite and 100% in the transatlantic group (P = 0.154). Median engagement times were 33.2 seconds (25th, 75th percentile: 24.9, 45.0 seconds) onsite and 26.7 seconds (25th, 75th percentile: 21.7, 35.5 seconds) transatlantic (P = 0.003). Median engagement time was faster for manual cases (17.1 seconds [25th, 75th percentile: 12.2, 23.2 seconds]) compared to both robotic groups (P < 0.001). Conclusions: In this preclinical study, the proof-of-concept for telerobotic ICA was successfully demonstrated. Furthermore, the current limits of telerobotic capabilities were tested by conducting ICA between separate continents and showing that transatlantic telerobotic navigation of endovascular devices is now technically possible.